REMOTE TRAINING AND CONTINUING EDUCATION - Alexander E. Petrov (Открытое образование (Москва), 2016)
In this paper we consider two trends in teaching methods and tools chosen on the base of continuing education concept and challenges of the information society. Indeed, the modern post-school education requires improved efficiency and activity of training as it should or can be combined with productive activity of students. Here we discuss and analyze some trends of contemporary distance learning in order to include them into solution of lifelong learning problems.